Peningkatan Keterampilan Menulis Cerita Pendek Melalui Strategi Area Isi (Studi Kasus Terhadap Mahasiswa Jurusan Bahasa dan Sastra Indonesia FBSS UNP) - Yasnur Asri (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
This research aims at identifying the effectiveness of the use of ‘content area strategy’ in teaching creative writing. Based on the action performed in the class it was found that the content area strategy was able to enhance students’ ability in writing short stories. The effectiveness was recognized from the average scores achieved in writing short stories both in describing the content of the story and the element of the story, and in language use.. Key words: short story, content area strategy